The Dualism of Tax Consultants’ Roles in the Taxation System - Yenni Mangoting; Retnaningtyas Widuri; Tonny Stephanus Eoh (Jurnal Akuntansi dan Keuangan, 2019)
The dualism of tax consultant's role as the agent of taxpayers and governments becomes a phenomenon in this research. Therefore, this research aims to understand the meaning of the dualism role of tax consultants in the taxation system. This study uses a qualitative approach to interpretive methods. The interpretive method assumes that reality does not stand alone but is constructed by the research subject. The method of data collection is done by interviewing two taxpayers and three tax consultants. The data analysis focused on the sentences and phrases that directly allude the researched phenomenon. The result of the research tells that there is an effort to balance the dualism of the role so that tax consultants can still protect the taxpayer’s interests, while ensuring that their services do not harm the nation. The balance of the dualism of the role is reflected into four meanings, namely: taxpayer advisors, mediators of taxpayer and government conflicts, aligning taxpayer and government relations and controlling taxpayer compliance